Ethical challenges in obtaining informed consent for the genomic study of rheumatic heart disease: a qualitative study - Masiye, Francis (Centre for Bioethics, 2016)
INTRODUCTION: Advances in genetic and genomic research have introduced new challenges in obtaining informed consent for research in low and middle-income settings. However, there are only few studies that have explored challenges in obtaining informed consent in genetic and genomic research in Africa and none in South Africa. To start filling this gap, we conducted an empirical study to investigate the efficacy of informed consent procedures for a genomic study on Rheumatic Heart Disease (RHDGen) at the University of Cape Town in South Africa. The main aim of the study was to understand the ethical challenges in obtaining informed consent in the RHDGen study. METHODS: We used a qualitative study methodology involving in-depth interviews and participant observations. Our research participants were RHDGen cases and controls as well as research staff involved in the recruitment of RHDGen research participants. In total, we conducted 32 in-depth interviews with RHDGen research participants, 2 in-depth interviews with research staff and 57 direct observations of the consent procedures of RHDGen research participants. The in-depth interviews were conducted in English, audio-recorded and transcribed verbatim. All the data were analysed using thematic content analysis. The study was conducted in 3 sites within Cape Town, South Africa, and these sites were the Groote Schuur Hospital in Observatory, the Vanguard Community Health Centre in Bonteheuwel and the Heideveld Community in the Cape Flats.